Addressing Differentiation in Live Human Keratinocytes by Assessment of Membrane Packing Order - Gutowska-Owsiak, Danuta; Podobas, Ewa I.; Eggeling, Christian; Ogg, Graham S.; Bernardino de la Serna, Jorge (Frontiers in Cell and Developmental Biology, 2020)
Differentiation of keratinocytes is critical for epidermal stratification and formation of a protective stratum corneum. It involves a series of complex processes leading through gradual changes in characteristics and functions of keratinocytes up to their programmed cell death via cornification. The stratum corneum is an impermeable barrier, comprised of dead cell remnants (corneocytes) embedded within lipid matrix. Corneocyte membranes are comprised of specialized lipids linked to late differentiation proteins, contributing to the formation of a highly stiff and mechanically strengthen layer. To date, the assessment of the progression of keratinocyte differentiation is only possible by determination of specific differentiation markers, e.g. by using proteomics-based approaches. Unfortunately, this requires fixation or cell lysis, and currently there is no robust methodology available to study differentiation in living cells, neither at a single cell, nor in high throughput. Here, we explore a new live-cell based approaches for screening differentiation advancement in keratinocytes, in a “calcium switch“ model. We employ a polarity-sensitive dye, Laurdan, and Laurdan general polarization function (GP) as a reporter of the degree of membrane lateral packing order or condensation, as an adequate marker of differentiation. We show that the assay is straightforward and can be conducted either on a single cell level using confocal spectral imaging or on the ensemble level using a fluorescence plate reader. Such systematic quantification may become useful for understanding mechanisms of keratinocyte differentiation, such as the role of membrane inhomogeneities in stiffness, and for future therapeutic development.